Fragments of bacterial endoglycosidase s and immunoglobulin g reveal subdomains of each that contribute to deglycosylation. - Dixon, E; Claridge, J; Harvey, D; Baruah, K; Yu, X; Vesiljevic, S; Mattick, S; Pritchard, L; Krishna, B; Scanlan, C; Schnell, J; Higgins, M; et al. (American Society for Biochemistry and Molecular Biology, 2014)
Endoglycosidase S (EndoS) is a glycoside-hydrolase secreted by the bacterium Streptococcus pyogenes. EndoS preferentially hydrolyzes the N-linked glycans from the Fc region of IgG during infection. This hydrolysis impedes Fc functionality and contributes to the immune evasion strategy of S. pyogenes. Here, we investigate the mechanism of human serum IgG deactivation by EndoS. We expressed fragments of IgG1 and demonstrated that EndoS was catalytically active against all of them including the isolated CH2 domain of the Fc domain. Similarly, we sought to investigate which domains within EndoS could contribute to activity. Bioinformatics analysis of the domain organization of EndoS confirmed the previous predictions of a chitinase domain and leucine-rich repeat but also revealed a putative carbohydrate binding module (CBM) followed by a C-terminal region. Using expressed fragments of EndoS, circular dichroism of the isolated CBM, and a CBM-C-terminal region fusion revealed folded domains dominated by β sheet and α helical structure, respectively. Nuclear magnetic resonance analysis of the CBM with monosaccharides was suggestive of carbohydrate binding functionality. Functional analysis of truncations of EndoS revealed that, whereas the C-terminal of EndoS is dispensable for activity, its deletion impedes the hydrolysis of IgG glycans.